Novel end-to-side one-layer continuous pancreaticojejunostomy vs. end-to-end invaginated pancreaticojejunostomy in pancreatoduodenectomy: A single-center retrospective study - Luo, Dong; Li, Yixiong; Ji, Liandong; Gong, Xuejun (Frontiers in Surgery, 2023)
Background and Objective Postoperative pancreatic fistula (POPF) is the most common critical complication after pancreatoduodenectomy (PD) and is the primary reason for increased mortality and morbidity after PD. We aim to investigate the clinical significance of a new end-to-side one-layer continuous pancreaticojejunostomy in PD. Methods The clinical data of 65 patients who underwent pancreatoduodenectomy surgery, at the Xiangya Hospital of Central South University from September 2020 to December 2021 were retrospectively analyzed. Results 40 patients underwent end-to-end invaginated pancreaticojejunostomy and 25 underwent the new end-to-side one-layer continuous pancreaticojejunostomy. No significant differences were observed in pancreatic fistula, intraperitoneal infection, intraperitoneal bleeding, reoperation, postoperative hospital stay, and perioperative death between the two groups. However, the new end-to-side, one-layer continuous pancreaticojejunostomy group had significantly shorter pancreaticojejunostomy time (32.6±5.1 min vs 8.3±2.2 min, p<0.001). The incidence of pancreatic fistula in the new pancreaticojejunostomy was 12%, including 2 cases of grade A POPF and only 1 case of grade B, and no grade C occurred. No deaths were observed during the perioperative period. Conclusions The new anastomosis method is less time-consuming compared with the traditional anastomosis method and did not increase the postoperative complication. In conclusion, it is a simplified and feasible method for pancreatic anastomosis.